Exogenous application of nitric oxide donors regulates short-term flooding stress in soybean - Khan,Muhammad Aaqil; Khan,Abdul Latif; Imran,Qari Muhammad; Asaf,Sajjad; Lee,Sang-Uk; Yun,Byung-Wook; Hamayun,Muhammad; Kim,Tae-Han; Lee,In-Jung (PeerJ, 2019)
Short-term water submergence to soybean (Glycine max L.) create hypoxic conditions hindering plant growth and productivity. Nitric oxide (NO) is considered a stress-signalling and stress-evading molecule, however, little is known about its role during flooding stress. We elucidated the role of sodium nitroprusside (SNP) and S-nitroso L-cysteine (CySNO) as NO donor in modulation of flooding stress-related bio-chemicals and genetic determinants of associated nitrosative stress to Daewon and Pungsannamul soybean cultivars after 3 h and 6 h of flooding stress. The results showed that exogenous SNP and CysNO induced glutathione activity and reduced the resulting superoxide anion contents during short-term flooding in Pungsannamul soybean. The exo- SNP and CysNO triggered the endogenous S-nitrosothiols, and resulted in elevated abscisic acid (ABA) contents in both soybean cultivars overtime. To know the role of ABA and NO related genes in short-term flooding stress, the mRNA expression of S-nitrosoglutathione reductase (GSNOR1), NO overproducer1 (NOX1) and nitrate reductase (NR), Timing of CAB expression1 (TOC1), and ABA-receptor (ABAR) were assessed. The transcripts accumulation of GSNOR1, NOX1, and NR being responsible for NO homeostasis, were significantly high in response to early or later phases of flooding stress. ABAR and TOC1 showed a decrease in transcript accumulation in both soybean plants treated with exogenous SNP and CySNO. The exo- SNP and CySNO could impinge a variety of biochemical and transcriptional programs that can mitigate the negative effects of short-term flooding stress in soybean.
Keywords: Soybean; Nitric oxide; Flooding stress; Sodium nitroprusside; S-nitrosoglutathione reductase; S-nitrosothiols